Development of polyethersulfone (PES) membrane for the treatment of aquaculture wastewater - Nurul Syazana Abdul Halim (Fakulti Sains dan Teknologi, 2012)
This study is to develop the polyethersulfone (PES) membranes with different preparation parameters in the treating aquaculture wastewater and in order to produce the PES membrannes with high selectivity as well as productivity